CHARACTERISTICS OF UNDERNOURISHED TODDLERS IN THE WORKING AREA OF BENGKULU CITY HEALTH CENTER - Kurnia Dewiani; Neng Kurniati; Nurhamidah Octarya; Linda Yusanti (Sean Institute, 2023)
Nutrition is an important element in supporting the growth and development of toddlers. Malnutrition is a condition of lack of nutrients needed including protein, carbohydrates, vitamins, and fats that can be assessed by the z-score growth index. This study is a quantitative descriptive study to identify the characteristics of undernourished and malnourished toddlers in the working area of Bengkulu City Health Center. The sample size was 53 respondents determined by purposive sampling technique consisting of 52 undernourished (wasted) respondents and 1 malnourished (severely wasted) respondent. The results showed that the dominant characteristics of more than half of the sample proportion were low mother’s education, mother’s occupation (mothers have no work), less eating pattern, and any history of child illness. More efforts are needed to minimize the factors associated with nutritional status in toddlers, especially in the community.